Analysis and Prediction of Terminal Temperature Using Motor Winding Temperature Compare with Ambient Temperature - สื่อเฉย บุญเลิศ; ดีสวัสดิ์ ไพรัตน์ (SAU JOURNAL OF SCIENCE & TECHNOLOGY, 2018)
This article analyzes and predicts the terminal temperature using motor winding temperature compare with ambient temperature by studying and testing the three phase electric motor and then analyzing and predicting the temperature at the terminal. Motor winding temperature with ambient temperature electric motors tested at 30 kW, 1,465 rpm. Tested without loading and loading. The terminal temperature to compare with ambient temperature to predict the terminal temperature of the electric motor winding and electric motors can work in full efficiency and to plan the maintenance of the electric motor before the damage.